2006
DOI: 10.2176/nmc.46.277
|View full text |Cite
|
Sign up to set email alerts
|

Perimesencephalic Nonaneurysmal Subarachnoid Hemorrhage Caused by Physical Exertion

Abstract: The clinical characteristics of perimesencephalic nonaneurysmal subarachnoid hemorrhage (SAH) caused by physical exertion were analyzed to investigate the causes and mechanisms of perimesencephalic nonaneurysmal SAH. Nine of 209 patients with spontaneous SAH were identified as having perimesencephalic nonaneurysmal SAH. Perimesencephalic nonaneurysmal SAH in four males and three females was precipitated by exertion. Age, sex predominance, type of exertion, symptoms, loss of consciousness during bleeding, clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…Patients with NNSAH tend to be male, younger and less hypertensive compared with those with aneurysmal SAH according to the current literature (6,13,23,42,52). The agerelated epidemiological data of our study cohort was in line with that of existing literature (mean age of 51 years); however, our study found no gender predominancy (51% to 49%).…”
Section: █ Resultssupporting
confidence: 88%
“…Patients with NNSAH tend to be male, younger and less hypertensive compared with those with aneurysmal SAH according to the current literature (6,13,23,42,52). The agerelated epidemiological data of our study cohort was in line with that of existing literature (mean age of 51 years); however, our study found no gender predominancy (51% to 49%).…”
Section: █ Resultssupporting
confidence: 88%
“…Possible sources include occult aneurysm, vascular malformation, intracranial arterial dissection, and cerebral venous thrombosis. 23,[27][28][29] Because of the high predictive value of the hemorrhage pattern on CT and the benign nature of perimesencephalic SAH, some authors advocate the need for only a single angiogram in those cases. 30 However, repeat angiography is almost always indicated in cases of non-perimesencephalic angiogram-negative SAH, because structural abnormalities such as aneurysms can be obscured on the first angiogram, which occurs in 4-30% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Although aneurysmal SAH is characterized by an aneurysmal source of SAH demonstrated on imaging, angiogram-negative SAH is characterized by an initial negative imaging work-up for aneurysmal source and may be associated with a wide variety of lesions including arteriovenous malformation (AVM), spinal AVM, venous anomaly, and so on. 4,[6][7][8][9][10][11][12][13][14][15] Perimesencephalic spontaneous subarachnoid hemorrhage (PMSAH) was originally characterized based on computed tomography (CT) SAH patterns that contained extravasated blood within the basal cisterns and around the midbrain, including a variant with blood only in the quadrigeminal cistern 16 and no identifiable source demonstrated on angiography. 17 PMSAH has been shown to represent approximately two-thirds of all cases of angiogramnegative spontaneous SAH.…”
Section: Introductionmentioning
confidence: 99%